2019
DOI: 10.1016/j.jid.2019.03.1130
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of STAT3 and RAD23B in Primary Sézary Cells to Histone Deacetylase Inhibitor FK228 Resistance

Abstract: FK228 (Romidepsin) and suberoylanilide hydroxamic acid (SAHA, Vorinostat) are FDAapproved histone deacetylase inhibitors (HDACi) for Cutaneous T-cell Lymphoma (CTCL), including the leukemic subtype Sézary Syndrome (SS). This study investigates RAD23B and STAT3 gene perturbations in a large cohort of primary Sézary cells and the effect of FK228 treatment on tyrosine phosphorylation of STAT3 (pYSTAT3) and RAD23B expression. We report RAD23B copy number variation in 10% (12/119; p ≤ 0.01) of SS patients, associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…More importantly, we further revealed that the downregulation of CFHR3 increased HCC cell growth and metastasis, which was suppressed by the STAT3 inhibitor, S3I-201. As known to us, phosphorylated STAT3 constitutes an essential pathway that regulates the signaling of miscellaneous biological activities including drug resistance, cell metastasis as well as cell proliferation [ 34 , 35 ]. In our study, we confirm that the phosphorylated STAT3 induced by CFHR3 downregulation suppressed p53 expression to promote HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we further revealed that the downregulation of CFHR3 increased HCC cell growth and metastasis, which was suppressed by the STAT3 inhibitor, S3I-201. As known to us, phosphorylated STAT3 constitutes an essential pathway that regulates the signaling of miscellaneous biological activities including drug resistance, cell metastasis as well as cell proliferation [ 34 , 35 ]. In our study, we confirm that the phosphorylated STAT3 induced by CFHR3 downregulation suppressed p53 expression to promote HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“… 83 Several other lines of evidence support that STAT3 plays a role in HDACi resistance: (1) STAT3 phosphorylation was associated with vorinostat resistance, 84 (2) JAK inhibition boosted the efficacy of romidepsin, 85 and (3) Sézary cells carrying the constitutively active variant of STAT3 (Y640F) were less sensitive to romidepsin-induced apoptosis. 86 Importantly, eradication of SE-producing S aureus by antibiotics inhibited STAT3 activation in vivo in patients with CTCL. 35 Taken together, these findings support the hypothesis that SE-producing S aureus can induce STAT3-dependent resistance to drugs such as HDACi.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic and genomic studies have recently provided data on the molecular mechanism for apoptosis resistance in CTCL malignant T cells and data on the molecular heterogeneity of CTCL cell populations ( Figure 2 ) ( 58 ). In one study, STAT3 and RAD23B genotypes were reported to influence primary HDACi sensitivity in Sézary cells ( 64 ). In another study, persistent activation of STAT1 and pSTAT3 was shown to correlate with resistance to vorinostat in patients with CTCL ( 65 ).…”
Section: Histone Modification In Ctclmentioning
confidence: 99%